Assessment of Reasons of Parents’ Refusal to Vaccinate Their Children - Jokubauskaitė, Greta; Galdikienė, Nijolė (Slauga. Mokslas ir praktika, 2021)
Abstract. Parents who do not have enough knowledge and scientifically based information about vaccines, their benefits and harms lead to the wrong approach to vaccination, they are beginning to question the usefulness of vaccines and it is necessary and completely refusing to vaccinate children so that there could be possible consequences. Research aim. To evaluate the reasons for parents refusing to vaccinate their children and possible consequences. Research methods. The study was performed using a quantitative descriptive research method. The study participants were parents (n = 394) who refused to vaccinate their children with at least one vaccine from the recommended pediatric preventive vaccination calendar. Results. The results of the study revealed that parents are aware of preventive vaccinations against infectious diseases, but only a third agree that preventive vaccinations are the main way to protect against infectious diseases. Usually, parents do not vaccinate their child for fear of vaccine complications; through an intensive vaccination calendar; due to excessive components in vaccines; because the child’s immunity in the event of an infectious disease is better than that acquired after vaccination; vaccinations can cause certain additional diseases and parents believe that vaccines are a way for companies to make money. Conclusions. False information about the safety of vaccines in the media and on the Internet has a major influence on parents’ decision to vaccinate their children. Due to insufficient information available and the wrong attitude about vaccination parents tend not to trust the benefits of vaccination. The main reasons why parents refuse to vaccinate their children are fears about vaccine complications and side effects, an over-intensive vaccination schedule, and the amount and impact of vaccine ingredients.